MEDIASI INTRINSIC MOTIVATION PADA ISLAMIC WORK ETHIC TERHADAP PERFORMANCE (FREELANCE KOTA BOGOR) - Alfina Hikmah Ramadhan; Fauzan Almanshur (INOVASI, 2023)
The development of digitalization has contributed to massive changes currently around the world, including in Indonesia. Technological developments also contribute to the work demands of HR (Human Resources) so it is necessary to know the ideal capacity size of an HR. The job performance aspect of an employee can influence the achievement of a company's goals so it requires further study. Furthermore, employee competency through the aspect of work ethic has a crucial role in shaping the change of an employee in today's massive era and to support components in adapting during the digitalization era is the role of Motivation. Motivation is needed because human nature requires some kind of persuasion, encouragement, or incentive to get better performance. This research analysis uses SEM (Structural Equation Model) with SmartPLS software version 3.0 as a statistical tool. This research aims to examine the effect of mediation by Intrinsic Motivation on Islamic Work Ethic (IWE) on Job Performance by taking a sample of 112 freelancers in creative fields in Bogor City. The results of the study show that Islamic Work Ethic (IWE) has a positive and significant effect on Job Performance, however, the Intrinsic Motivation aspect is unable to mediate either directly or indirectly.